Deep learning for bias correction of MJO prediction - H. Kim (Nature Portfolio, 2021)
The Madden-Julian Oscillation (MJO) is a crucial component of the tropical weather system, but forecasting it has been challenging. Here, the authors present a deep learning bias correction method that significantly improves multi-model forecasts of the MJO amplitude and phase for up to four weeks.